Faktor-Faktor Yang Mempengaruhi Kinerja Perawat Dalam Pemberian Pendidikan Kesehatan Studi Fenomenologis di Puskesmas I Sokaraja - Purwo, Viana Yuni; Suroso, Jebul (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Health education aims to change people's unhealthy behaviour to healthy behaviour. Act No. 36 of 2009 stated that health is human rights and one of the well-being elements which must be realized in accordance with the ideals of the nation. Nurses in Puskesmas are considered agents of change of peoples health level.Thus, they play an important role in providing health education. There are several factors affecting nurses performance in providing health education to either patients or patients family and the people in their working area.Objective: This research aims to identify factors affecting nurses' performance in providing health education. Method: This research is a qualitative research using phenomenological study approach. There are 7 nurses as the research sample. The sampling is purposive sampling, in which the size of individual key person or participant has been determined before the data collection. The sample size is determined based on the saturation theory.Result: The research result shows that the effect of external motivation factor is more dominant in providing health education. The participants workload does not increase by providing health education. Meanwhile, compensation does not fully affect in providing health education.Conclusion: Factors of motivation and compensation affect the nurses' performance while the factor of workload does not affect the nurses' performance in providing health education.